2023
DOI: 10.1177/21582440231178713
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Testing the Negative Mentoring Experience Questionnaire (NMEQ) for Nurses

Abstract: Many nurse managers actively developed mentoring programs to shorten the acclimation period of new nurses in hospitals. The main aim was to develop a negative mentoring experience questionnaire (NMEQ) and test its validity and reliability. A cross-sectional study was employed. This study adopted questionnaire-survey method with new nurses of Taiwanese hospitals. In the main study, this study adopted reliability analysis, content, validity, construct validity and criterion-related validity analysis. 255 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Sometimes there are negative experiences stemming from relational dynamics, specific mentoring processes and the broader hospital context. These findings are consistent with findings from Huang et al (2023), who identified dimensions of negative mentoring as mentor, mentee and management-oriented factors in their quantitative study done among nurses. The problems arising from relational dynamics resulted in behaviours that were considered inappropriate for the normative functioning of the mentoring relationship.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Sometimes there are negative experiences stemming from relational dynamics, specific mentoring processes and the broader hospital context. These findings are consistent with findings from Huang et al (2023), who identified dimensions of negative mentoring as mentor, mentee and management-oriented factors in their quantitative study done among nurses. The problems arising from relational dynamics resulted in behaviours that were considered inappropriate for the normative functioning of the mentoring relationship.…”
Section: Discussionsupporting
confidence: 91%
“…Challenges in mentoring can stem from relational dynamics, specific mentoring activities or the broader work environment-the hospital. From a functional perspective, mentoring challenges manifest in various ways: a complete lack of mentorship, mentors being inaccessible or the presence of mentors without the appropriate qualifications (Huang et al, 2023;Wissemann et al, 2022). Mentors often cite challenges such as heavy workloads, time constraints, competing priorities, mentees who are reluctant to learn and a general negative attitude of new graduates towards the nursing/midwifery profession (Merga et al, 2020;Rohatinsky et al, 2020).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Leaders from Taiwan referenced a mentee story that was given great attention in Taiwan, emphasizing the importance of mutual communication, respect, and recognition with strong encouragement by mentors 33. Indeed, in a study in Taiwan,34 the characteristics of bad mentees included “poor response,” “poor communication,” and “too serious self-defense.” The leaders from South Korea also emphasized effective communication between the mentors and the mentees. One of the leaders said that good mentees would be active learners and good communicators who seek the mentors' advice frequently, and good mentees would seek advice from their seniors and peers in advance.…”
Section: Current Status Of Research Mentoring In Nursingmentioning
confidence: 99%